PPM1G Inhibits Epithelial–Mesenchymal Transition in Cholangiocarcinoma by Catalyzing TET1 Dephosphorylation for Destabilization to Impair Its Targeted Demethylation of the CLDN3 Promoter - Wenzheng Liu; Yiyang Kuai; Da Wang; Junsheng Chen; Fei Xiong; Guanhua Wu; Qi Wang; Wenhua Huang; Yongqiang Qi; Bing Wang; Yongjun Chen (Advanced Science)
Abstract Ten–eleven translocation protein 1 (TET1) functions as an epigenetic regulatory molecule, mediating the majority of DNA demethylation, and plays a role in the development of different types of cancers by regulating the expression of proto‐oncogenes and oncogenes. Here it is found that TET1 is highly expressed in cholangiocarcinoma (CCA) and is associated with a poor prognosis. In addition, TET1 promotes claudin‐3 (CLDN3) transcription by targeting the CLDN3 promoter region between −16 and 512 for demethylation. PPM1G functions as a protein dephosphorylase, catalyzing the dephosphorylation of TET1. This results in the destabilization of the TET1 protein, thereby impairing the targeting of the CLDN3 promoter for demethylation. Two phosphatase inhibitors, staurosporine and AZD0156, inhibit epithelial‐to‐mesenchymal transition (EMT) in cholangiocarcinoma cells by suppressing TET1 expression. In conclusion, it is also demonstrated that PPM1G can be employed as a therapeutic target to impede the progression of CCA by catalyzing the dephosphorylation of TET1, which diminishes the capacity of TET1 to target the CLDN3 promoter to activate transcription and inhibit EMT in CCA.